2016
DOI: 10.1109/tgrs.2015.2452812
|View full text |Cite
|
Sign up to set email alerts
|

Total-Variation-Regularized Low-Rank Matrix Factorization for Hyperspectral Image Restoration

Abstract: In this paper, we present a spatial spectral hyperspectral image (HSI) mixed-noise removal method named total variation (TV)-regularized low-rank matrix factorization (LRTV). In general, HSIs are not only assumed to lie in a low-rank subspace from the spectral perspective but also assumed to be piecewise smooth in the spatial dimension. The proposed method integrates the nuclear norm, TV regularization, and L 1 -norm together in a unified framework. The nuclear norm is used to exploit the spectral low-rank pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
346
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 554 publications
(347 citation statements)
references
References 44 publications
1
346
0
Order By: Relevance
“…Total variation (TV) has been widely used to explore the spatial piecewise smooth structure for tackling various HSI processing tasks [15,28,29]. It has the ability of preserving local spatial consistency and suppressing observed noise.…”
Section: D Tv Regularizationmentioning
confidence: 99%
“…Total variation (TV) has been widely used to explore the spatial piecewise smooth structure for tackling various HSI processing tasks [15,28,29]. It has the ability of preserving local spatial consistency and suppressing observed noise.…”
Section: D Tv Regularizationmentioning
confidence: 99%
“…However, when only using spectral information, a single representation coefficient vector of the target pixel can only provide limited discriminative information [31,32]. Based on the fact that pixels within a local patch (where the center pixel is the target pixel to be processed) have a high probability of being associated with the same thematic class, the sparse representation coefficients of these pixels are also expected to be similar.…”
Section: Incorporating Spatial Information With the Spatial Max Poolimentioning
confidence: 99%
“…Hongyan et al [19] introduced a new hyperspectral imagery restoration method based on the low-rank matrix recovery, which suggested that a clean hyperspectral imagery patch can be regarded as a low-rank matrix. Wei et al [20] proposed a method that integrates the nuclear norm, TV regularization and the 1 norm into a unified framework. The nuclear norm is used to exploit the spectral low-rank property, and the TV regularization is adopted to explore the spatial piecewise smooth structure of the hyperspectral imagery.…”
Section: Generalized Rsi Reconstructionmentioning
confidence: 99%